The Representation of the Islamic Religious Leader in Film “Makmum” by Riza Pahlevi - Jordy Satria Widodo (Universitas Pakuan, 2022)
The film is known as the audio-visual means of communication. Moreover, it encompasses so many genres, especially horse horror films film has been well-known in the context of Indonesia’s film production. Horror films have a tight bond with the Indonesian audience since most people believe in mystical and supernatural occurrences. The existence of the religious leader becomes important to drive out the ghosts from hauntings. Maximum by Riza Pahlevi is one horror film that portrays the coming of the Islamic religious leader as the problem solver over the haunting problems in the movie. The purpose of this research is to analyze the representation of the Islamic religious leader in the film Makmum by Riza Pahlevi. The research made use of a qualitative approach and took the denotative and connotative semiotics concept by Roland Barthes. The data collection technique was conducted through document analysis. The research result presented that the images of the Islamic religious leader comprise having a deep Islamic religious knowledge, becoming loyal to the teachings, and becoming righteous according to religious beliefs shown through varied scenes in the movie.Keywords: Horror Films; Representation; Semiotics; The Islamic Religious Leader.